Integrating Problem-Based Learning into the Chinese Language Classroom Curriculum Design in Malaysian Chinese Independent High Schools - Chsing, Lim Chsing; Ling, Loh Yoke; Yi, Chia Tze (Journal of Posthumanism, 2025)
Educational reformation has struggled with the persistent issue of encouraging independent learning abilities among high school students. Students have been vocal about respective disappointment with Chinese language classes and textbooks in recent years, including the lack of motivation. Student learning quality diminishes when only a single teaching method is employed. Therefore, teachers should reappraise the curriculum design to emphasise developing personal learning abilities among students for higher classroom engagement. Teachers should redefine the concept of self-directed learning by expanding the definition of self-sustaining student learning behaviour outside classrooms before altering the existing approach to classroom learning. Although PBL remains in the early stages of CLC curriculum design, the problem-based learning (PBL) method could assist in addressing the Chinese language classroom (CLC) learning issues. The current study examined the PBL approach in CLCs and developed a framework for educating a Chinese language unit to second-year students in a Malaysian private high school. In addition, this study provided the Malaysian government with a strategic recommendation for improving the primary school curriculum.